2019
DOI: 10.18733/cpi29481
|View full text |Cite
|
Sign up to set email alerts
|

Teacher-Centered vs. Student-Centered

Abstract: Wright (2011) distinguishes between teacher-centered and student-centered learning approaches along a spectrum of five dimensions: power balance, course content function, teacher and student roles, responsibility for learning, and assessment purposes and processes. Based on Wright’s framework, this study explores students’ perceptions of their experience with teaching methods at Uganda’s Makerere University. Specifically, the investigation uses a mixed-methods research approach that combines survey data with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 13 publications
2
38
0
1
Order By: Relevance
“…Thus Type 16 is the most serotype involving in HPV infections among the average Iranian population (2,6,7,8). It appeared as the type of HPV infections with the most frequency in our study (14.8%) and seemed to have more severe exudates.…”
Section: Dear Editorsupporting
confidence: 44%
“…Thus Type 16 is the most serotype involving in HPV infections among the average Iranian population (2,6,7,8). It appeared as the type of HPV infections with the most frequency in our study (14.8%) and seemed to have more severe exudates.…”
Section: Dear Editorsupporting
confidence: 44%
“…However, the students also had a high level of agreement that active learning was a better test of their learning. Along those lines, Muganga and Ssenkusu (2019) found that teacher-centered methods defined as "lecture, handouts/slides/syllabus content, and teacher-directed reading/viewing" (p. 28), were more frequently used by professors than studentcentered methods. Mathew and Pillai (2016) found that nursing students indicated that they preferred the lecture method as compared to peer teaching, demonstrations, or discussion.…”
Section: Review Of the Literature Teaching Methodsmentioning
confidence: 99%
“…Based on prior research (Garrett, 2008;Muganga & Ssenkusu;2019;Smaldino et al, 2015), the 27 items were either identified as teacher-centered (e.g., lecture where professor talks with no visuals, watching a film), or student-centered (e.g., experiential activities, free flowing classroom discussion). In addition, the investigators' experience in different academic majors (i.e., business, sports and exercise science, and educational psychology) led to identifying some teaching methods as a combination of both (e.g., lecture where professor talks with student interaction, demonstrations, and practice) (Table 2).…”
Section: Student Preferences For Teaching Methodsmentioning
confidence: 99%
“…This approach to learning is in accordance with the first of six strategies of Harden SPICES model for curriculum development, which is a student-centered and not a teacher-centered approach (S) (7,8). In conclusion, the results from medical students and the Knowles' Andragogical Model as a theoretical lens, is expected to help medical education experts with emphasizing on a student-centered approach in medical education curriculum in order to prepare future physicians for meeting unexpected healthcare crisis demands.…”
Section: Dear Editormentioning
confidence: 99%